Genetic Epidemiology in Germany - Wichmann, H.-E. (Methods of Information in Medicine, 2005)
Objectives: Genetic epidemiology investigates the role of genetic factors and their interaction with environmental factors (in a broad meaning) for the occurrence of diseases in human populations. Its aim is to undest-and the influence of genetics on the development of dis-eases, their course and the clinical implications, with the final goal to improve prevention, diagnostics and therapy.Methods: Originally genetic epidemiology was understood as a specialized discipline with the main focus on family-based studies. The extraordinary development of genetics in the last decades – with respect of the understanding of the meaning of genes for human health, as well as by the availability of cost-effective high throughput methods in the lab, has opened enormous opportunities to study genetic factors. Now, genetic epidemiology and genetic statistics have a much broader application. In addition, access to large samples of patients or from the population is needed. This can be realized via biobanks.Results: Large biobanks with 500,000 or more patients or participants from the general population are being established or planned in the UK, Japan or the US. However, in Germany only two smaller activities are ongoing, KORA-gen in the south and POPGEN in the north. Possibilities to reach larger numbers, based on existing cohorts or disease networks are discussed. Ethical boundary conditions have to be taken into account, which seem to improve due to the Opinion of the German National Ethics Council on Biobanks for Research. Furthermore, the activities of the German centers for Genetic Epidemiological Methods (GEMs) as research and support units for genetic statistics and epidemiological methodology are described.Conclusions: Genetic epidemiology is based strongly on interdisciplinary collaboration and includes basics of genetics, elements of molecular biology to identify genes, population genetics, clinical medicine, and methodological disciplines as epidemiology, biostatistics and bioinformatics. In Germany the situation for this type of patient-based research has recently improved due to the National Genome Research Network (NGFN).
Keywords: Biobanking; genetics; epidemiology; bioethics